Atlas of Frog and Toad Diversity in Paliyan Gunungkidul Wildlife Sanctuary the Android Based as a Biological Learning Media - Choirudin, Faris; Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2022)
Ordo Anura (frogs and toads) is one of the orders in the amphibious class, which rarely gets attention. Still the lack of supporting references to learning about frogs and toads causes the learning process to be focused only on books and teacher's explanation, thus resulting in a lack of knowledge about the diversity of frogs and toads around it. This research aims to find out what types of frogs and toads, as well as find out the index of diversity of frogs and toads that spread in the Paliyan Gunungkidul Wildlife Reserve Area, find out the results of the identification of the Paliyan Gunungkidul Wildlife Reserve, and develope an android based atlas/application of frog and frog diversity (order anura) in the Paliyan Gunungkidul Wildlife Reserve as a biological learning. This research consists of two stages, there are the study of frogs and frogs in the Paliyan Gunungkidul Wildlife Sanctuary using exploratory descriptive methods and combined with Visual Encounter Survey (VES) and pacth medode to determine sampling point and development stage of frog and frog diversity atlas with R&D development method according to Borg and Gall. Frog and frog diversity research resulted in 7 species divided into 5 families with at three stations in the Paliyan Gunungkidul Wildlife Reserve area. Atlas/application is assessed by 1 material expert, 1 media expert, and 1 biology teacher. Product quality assessment data obtained from the sheet in the form of questionnaires. The results of the material expert assessment said it falls into a very decent category with an average percentage of 89.58%, assessments from media experts are included in the decent category with a percentage of 82.91%, assessments by biology teachers fall into the category of very decent with an average percentage of 90.4%, and assessments from students obtain an average percentage of 86.55% which shows the category is very feasible. Based on this assessment, it can be noted that atlas based android/application frogs and frogs is worth using as a medium of biological learning.